Harmonization between Investigators and Advocates in the Law Enforcement Process - Kafrawi, Rachman Maulana; Mohammad Zamroni; Marsal, Antonino Pedro (Magister of Law, Faculty of Law, University of Mataram, 2023)
Law enforcement containing the proportional principle is how law enforcement runs in such a way, so that it does not only enforce the normative rules (aspects of legal certainty) but also the philosophical aspects (aspects and values of justice). Functional differentiation causes law enforcement practices by law enforcement officers to be fragmented and fragmentary because each component of law enforcement has different perceptions and meanings. This has an impact on the difficulty of realizing an integrated and integrated criminal justice system because there are often conflicts of interest and differences in interpretation between law enforcement components so that the products of the judiciary have not been able to meet the expectations of the people seeking justice. So in this systematic framework, the actions of one body will affect the other bodies. Research purposes namely analyzing the harmonization between investigators and advocates in the law enforcement process and analyzing the harmonization and synchronization between law enforcers. The research method in this case combines elements of normative law which are then supported by additional data or empirical elements. The system in the criminal justice system so that in practice it will have an effect on the implementation of the criminal justice system as a whole.